PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN PURBALINGGA - Yuliantika, Dewi; Pratiwi, Agustin Riyan; Ulya, Widadatul (DFAME Digital Financial Accounting Management Economics Journal, 2023)
he Regional Drinking Water Company (PDAM) of Purbalingga Regency has received criticism and complaints from customers regarding the quality of service which is considered unsatisfactory. Based on observations and data obtained, there were 1,095 customer complaints from PDAM Purbalingga regarding pipe leaks or damage, water flow congestion and other problems. In addition, the employees of the Purbalingga Regency PDAM received less encouragement from the leadership and there were several employees of the Purbalingga Regency PDAM from various divisions who left their jobs or did not come to work. This study aims to determine the extent to which the influence of leadership variables, work motivation and organizational culture affect employee performance. This study used a descriptive method with a quantitative approach with the help of SPSS version 26.0. This study used multiple linear regression analysis. The size of the number of samples in this study was determined using the slovin formula, so that the sample used was 61 respondents from PDAM Purbalingga Regency. Primary data collection using a questionnaire. The sampling technique uses simple random sampling. The results of this study indicate that the leadership variable has no effect on employee performance with a significant value of 0.562, the work motivation variable has no effect on employee performance with a significant value of 0.067, and the organizational culture variable has a positive and significant effect on employee performance with a significant value of 0.000. Employee performance can run well if the company can provide leadership, motivate employees and create a good organizational culture.